Polyphenol content of Marasca sour cherry ecotypes (Prunus cerasus Marasca) and its stability during freezing storage - Pedisić, Sandra (Array, 2019)
The present research was undertaken to evaluate the polyphenol content of two Marasca sour cherry ecotypes (Recta and Brač 2) grown in two areas in Croatia (Zadar and Split), their stability during freezing storage at -18 °C for six months and contribution to antioxidant capacity (AOC), respectively. Polyphenolic content was assessed by high performance liquid chromatography (HPLC UV/VIS PDA) and anthocyanins (ANT), hydroxycinnamic acids (HCA), flavonol glycosides (FG) and flavanols (FLAV) were determined. ANT dominated in fresh and frozen cherry ecotypes (321.90 – 774.61 mg/100 g dm) and cyanidin-3- glucosylrutinoside (CYGR) was present in the highest concentration (223.22 – 501.04 mg/100 g dm). The contents of other phenolics were considerably lower compared to ANT: HCA=40.72 – 86.28 mg/100 g dm, FG=22.34 – 41.03 mg/100 g dm and FLAV=0.16 – 0.59 mg/100 g dm, where major compounds presented in HCA were p-coumaric and neochlorogenic acids, in FG quercetin-3-glucoside and in FLAV catehin. Furthermore, statistical analysis showed that all sour cherry samples significantly differed according to the ANT, HCA, FG and FLAV content (p≤0.01). Generally, ecotype Recta and Zadar growing area had higher polyphenolic content. Freezing storage caused decrease of almost all polyphenolic groups, particularly ANT (16 – 30 %) and HCA (26 – 36 %) while better stability of FG (10.5 – 20 %) and higher variation of FLAV content was observed. For determination of AOC three methods (DPPH, FRAP, ABTS) were used and the AOC was as follows: DPPH=3.284 – 6.38 mmol TE/100 g dm, FRAP=7.18 - 18 mmol TE/100 g dm and ABTS=73.16 - 119.93 mmol TE/100 g dm. The results indicate higher AOC in samples of Brač 2 ecotype from Zadar growing area.